Productive performance and economic evaluation of tilapia stocked in different times of the year - Costa, Jesaias Ismael da [UNESP]; Sabbag, Omar Jorge [UNESP]; Silva Ayroza, Luiz Marques da; Espagnoli Geraldo Martins, Maria Inez [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2017)
This study aimed to determine production cycles based on the stocking period and the influence of the cycles on productive performance indices, production costs, and profitability. The present study was carried out on a fish farm located in Palmital -SP, Brazil, which consists of 2706 m(3) of net cages with an annual production of 400 tons of tilapia and regular harvests throughout the year. Production data, investment and expenditures were obtained by using a semi-structured questionnaire to calculate the total operational costs and profit indices. All monetary values of invested items have been corrected by the General Price Index (GPI) for December 2014. Three rearing phases were identified and characterized as the nursery, pre-finishing, and finishing phases. The production cycle is between 195 and 270 days and the profitability index is between 15.08 to 26.09%, in which the best production scenario is found when carrying out all of the rearing stages ( nursery, pre-finishing, and finishing) in high temperatures. The stocking fish in low temperatures increases the production time by 38.46%. The extend production time allow the producer to regularly offer the product and have more flexibility on the decisions of the production
Keywords: fish farm; production costs; profitability; temperature